Art and Divine Order in the Divina Commedia - Jongeneel, Els (Literature and theology, 2007)
The present essay focuses on a conflict between ethics and aesthetics in the Divina Commedia, and on the way in which Dante has tried to resolve it. Although bound up with a Christian view on History, he embeds, as a self-conscious modern artist, his secular stil novo poetics of earthly love in God's salvation plan for humankind. This conflict requires a relatively long ‘journey’ of interpretation and reconsideration, illustrated by concrete ‘case-studies’, the most famous being that of Francesca of Rimini in Inferno V. In accordance with medieval hermeneutics, Dante makes use of a palinodic dialectic in order to reconcile profane art with divine order.